Mandombe - Pasch, Helma (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
Mandombe, one of the most recent modern African scripts, was originally designed to write the Bantu languages of the Congos, and eventually all languages on the continent. Its symbols are made of simple and composite geometrical forms which predate the script. It is apparently the only African script which has gained some social success without any political support.